URGENSI PSIKOLOGI DALAM PROSES DAKWAH - St. Rahmatiah (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
Da'wah is an attempt to influence others to act and behave like what is desired by Dai. As psychological beings, humans are creatures of thought and wills and human beings have a different way of thinking and feeling with each other. Therefore, it is necessary to understand how Mad'u that what is delivered by dai easily been well received. Preaching with the psychological approach (persuasive) allows people to follow the will of the Mad'u, but they felt was following the will of itself.